Drying and storage of ’Cleopatra’ mandarin seeds - Villegas-Monter, Angel; Andrade-Rodríguez, María (Pesquisa Agropecuaria Brasileira, 2005)
The objetives of this work were to evaluate the effect of the treatment with chemical products and the humidity content for conservation of seeds of 'Cleopatra' mandarin (Citrus reshni Hort ex Tan). Seeds with 14.7% of moisture content were treated with four fungicides and 8-hydroxyquinoline and stored at 4±2°C for one year. Three groups of seeds with 5.0, 14.7% and 26.8% of moisture content were stored as above. Germination and emergence were evaluated at the beginning of the two experiments, at six and twelve months of storage. In the test with chemical products, storage of seeds with 14.7% of moisture content was possible only for six months, with higher percentages of germination and emergence (59.3% and 54.0%, respectively), while in seeds without chemical treatment percentages of germination and emergence were about 33.3% and 27.3%, repectively. As far as the moisture content of the seed is concerned, at six months of storage the highest seedlings emergence (63,6% and 58.0%) were obtained, in seeds with 26.8% and 5% of moisture, respectively. Twelve-months-seeds with 5% of moisture content caused 75.6% of emergence.